2015
DOI: 10.21608/mjfmct.2015.47277
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporosis and the Duration of Coca•Cola Consumption Relationship in Female Albino Rats

Abstract: Coca-cola beverage is one of the risk factors resulting in calcium deficiencies and an increased risk of osteoporosis in rats. The objective of this study is the comparing between five and seven months of coca-cola consumption on osteoporosis markers. The obtained data suggested that orally coca-cola consumption (5ml/Kg/day) cause a significant increase in minerals (calcium and phosphorus) level, in both serum and urine while a significant decrease in the level of these minerals in bone was recorded specially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…These EDX results are supported by previous study that explained that excessive soft drink consumption have been found to be associated with low BMD and bone fractures. Decrease in bone minerals (calcium and phosphorus) accompanied with an increase in their levels in serum and urine plays a major role in the genesis of Coca-Cola-associated bone loss (4) . Moreover, Garcia et al recorded subsequent hypocalcaemia and loss of femoral BMD in ovaryectomized rats received cola (24) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These EDX results are supported by previous study that explained that excessive soft drink consumption have been found to be associated with low BMD and bone fractures. Decrease in bone minerals (calcium and phosphorus) accompanied with an increase in their levels in serum and urine plays a major role in the genesis of Coca-Cola-associated bone loss (4) . Moreover, Garcia et al recorded subsequent hypocalcaemia and loss of femoral BMD in ovaryectomized rats received cola (24) .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, increased phosphoric acid and caffeine content in Coca-Colas are responsible for the increase in the acidity in the body, which in consequently affect the Ca/P ratio and bone mineral content. Moreover, soft drinks rich in caffeine, phosphoric acid, and fructose leads to interference with Ca absorption contributing to Ca imbalance leading to more Ca loss (4) . Prolonged intake of caffeinated and decaffeinated Coca-Cola drinks leads to bone resorption in humans with hazardous effects on the protein intake.…”
Section: Introductionmentioning
confidence: 99%